Stepping stones triple p and acceptance and commitment therapy for parents of children with cerebral palsy: Trial protocol - Whittingham, K.; Sanders, M.; McKinlay, L.; Boyd, Roslyn (2013)
This project aims to optimise outcomes for children with cerebral palsy (CP) and their families by testing the efficacy of two complementary interventions novel to the CP population: (1) parenting intervention (Stepping Stones Triple P, SSTP); and (2) parental stress management (Acceptance and Commitment Therapy, ACT) tailored for parents of children with CP. The efficacy of SSTP and the additional effects of ACT will be tested in a wait-list randomised controlled trial, with parents of children with CP (N = 110) randomised into three groups; SSTP, SSTP + ACT and wait-list control. Intervention delivery will combine group sessions with phone consultations. Outcomes will be assessed post-intervention with retention of effect examined at 6-month follow-up. Child outcomes will include: externalising behaviour (primary child outcome), functional performance, parent-reported child quality of life; and parent outcomes will include: dysfunctional parenting (primary parent outcome), parental confidence in performing disability-related parenting practices, degree of problems in performing disability-related parenting practices, parental adjustment, psychological flexibility and parental attitude to child emotions. The theoretical background, study design and study procedures are discussed. The validation of a parenting intervention and a parenting stress intervention for parents of children with CP is crucial to better support parents of children with CP in their parenting role and in providing evidence-based intervention for behavioural and emotional problems in children with CP. Copyright © The Author(s), published by Cambridge University Press on behalf of Australian Academic Press Pty Ltd 2013.